A comparison Between Two Etchants Used to Etch Surface of CR-39 Nuclear Track Detector - Hussein, B. J. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The search included a comparison between two etchands for etch CR-39 nuclear track detector, by the calculation of bulk etch rate (Vb) which is one of the track etching parameters, by two measuring methods (thichness and change mass). The first type, is the solution prepared  from solving NaOH in Ethanol (NaOH/Ethanol) by varied normalities  under temperature(55ËšC)and etching time (30 min) then comparated with the second type the solution prepared from solving NaOH in water (NaOH/Water) by varied normalities with (70ËšC) and etching time (60 min) . All detectors were irradiated with (5.48 Mev) Î±-Particles from an 241Am source in during (10 min). The results that Vb would increase with the increase of the normality of etchant until we arrive to the upmost value at (2N) then it would decrease, where (40.116 Î¼m/h)and (40.313Î¼m/h) were for both of the methods consecutively , and when compared with etchant of (NaOH/ Ù‹ â—ŒWater) was (1.416Î¼m/h) and (1.429Î¼m/h) consecutively.